The collapse of Gaddafi regime and the democratic changes in Libya: A study from al Siyasah al-Syar’iyyah perspective / Elyas Abobaker A. Elbarouni - Elyas Abobaker , A. Elbarouni (2018)
This study investigates the nature of the democratic transition in Libya following the 17th February revolution in 2011, leading to the fall of Gaddafi's regime. It attempts to draw the characteristics of the revolution within the framework of Alsiyasah Al-syarʻiyyah The aims of the study are to determine the causes and motives of the Libyan revolution in February 2011 and the problems of democratization; to determine the role of the Libyan political elite in the democratic transition following the February revolu-tion in Libya; to identify the most important internal and external determinants affecting the process of democratization in Libya; and to illustrate a future vision of the demo-cratic transition of the Libyan political scene after the revolution from the perspective of Alsiyasah Alsyarʻiyyah. The researcher adopts a descriptive approach based on observa-tion and a historical tracking of the related events. The study concludes that the revolu-tion in Libya was initiated by the people and aimed at eliminating the Gadhafi regime, which undermined the values of the Libyan society and distorted its political culture. The democratic transition in Libya requires a long period of treatment of the negative impacts resulting from Gaddafi’s rule in the light of Alsiyasah Alsyarʻiyyah, i.e. the God’s governance, justice, equality and Shura (democracy). The researcher suggests preparing a constitution which creates alliances between different political parties. The Shariah sustain and further the national and Islamic principles. It is also suggests high-lighting the role of the wasatiyyah in the process of democratic transition of the Libyan state represented in the language of religious discourse through different media and mosque platforms.